Differences of Macroalgal Consumption by Eight Herbivorous Coral Reef Fishes From the Xisha Islands, China - Wu, Peng; Wang, Teng; Liu, Yong; Li, Chunhou; Xiao, Yayuan; Xu, Shannan; Han, Tingting; Lin, Lin; Quan, Qiumei (Frontiers in Marine Science, 2022)
Herbivorous fishes play an important role in preventing the overabundance of macroalgae on coral reefs. Understanding the feeding selectivity and consumption of macroalgae by herbivorous fishes can be challenging in studies of their ecological role in the preservation and recovery of coral reefs. Coral reef decline, macroalgal overgrowth and overfishing are clearly visible in the Xisha Islands, China. However, there are seldom studies on the feeding behaviors of herbivorous fishes in this area. We used microscopy, 18S rRNA high-throughput sequencing, and stable isotope analyses to comprehensively examine the diet of eight herbivorous reef fish species common in the Xisha Islands, including one parrotfish, two chub, two unicorn fish, and three rabbitfish. Based on microscopic examination, Siganus argenteus fed on the highest number of macroalgae species (five species), followed by Naso unicornis (four species). Kyphosus cinerascens, K. vaigiensis, N. unicornis and S. punctatissimus fed on the entire macroalgal thallus, indicating their greater ecological importance compared with species that only consume algal fronds. According to the 18S rRNA high-throughput sequencing of fish intestinal contents, cluster analysis revealed that consumed macroalgae composition from the eight fishes always grouped together based on the fish species, but with low similarity. K. vaigiensis removed the highest diversity of macroalgae species as well as the greatest quantity of macroalgae. Calotomus carolinus can consume the red alga Pneophyllum conicum, which is widely distributed on Indo-Pacific coral reefs and can overgrow and kill live corals. N. unicornis was found to occupy the lowest trophic position based on stable isotope analysis. Multi-technique analyses revealed that K. vaigiensis, N. unicornis and S. argenteus showed a high consumption potential of macroalgae, suggesting that they are the key browsers that should receive priority protection in the Xisha Islands. A diverse herbivorous fish fauna is also very important in the Xisha coral reefs. These results not only demonstrated the various functions of different herbivorous fish species in macroalgal removal, but also provided insights into the management of herbivorous fishes on the coral reefs of the South China Sea.